Perceptions of Pain in Breast Cancer Patients (Research, Society and Development, 2021)
Objective: to analyze in scientific publications evidence that describes the perception of pain in women with breast cancer. Methodology: this is a descriptive study carried out through an integrative review, with a qualitative approach and content analysis by Bardin, in the light of the theoretical framework of Cicely Saunders. In the methodological path of the categorization process, to choose the categories we adopted the semantic criterion that advocates the selection based on themes. Results: the sample consisted of 14 articles, classified in levels of evidence according to the Oxford Center for Evidence-based Medicine, where 3 studies (21.43%) were classified as high level of evidence, research with moderate level represented 9 of the articles (64.28%) and with a low level of evidence for clinical practice, 2 articles (14.28%). Conclusion: the present study demonstrated a highlight for the valorization of physical pain, this fact is a portrait of a culture of care supported by the biomedical model and medicalization, based on that, emotional / mental and social / family pain was less contextualized, whereas spiritual pain was not mentioned, leading us to reflect on the concept of total pain, which should not be neglected in women with breast cancer.